2021
DOI: 10.1017/jfm.2021.272
|View full text |Cite
|
Sign up to set email alerts
|

Collective bursting of free-surface bubbles, and the role of surface contamination

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 68 publications
1
38
0
Order By: Relevance
“…The tank, with dimensions L60 × W60 × H25 normalcnormalm3 ${\mathrm{c}\mathrm{m}}^{3}$, is open at the top, leaving the bubbles unconstrained once they reach the surface (Figure 1a). A top‐down imaging allows for a direct measurement of their location and size, as illustrated in Figures 1b–1e and detailed in a recent study focusing on the surface bubble dynamics (Néel & Deike, 2021). Drops, produced by the bursting surface bubbles, are imaged and detected from the side by means of telecentric shadow imaging, which preserves the true drop size across the depth of field.…”
Section: Contamination Controlled Optimal Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tank, with dimensions L60 × W60 × H25 normalcnormalm3 ${\mathrm{c}\mathrm{m}}^{3}$, is open at the top, leaving the bubbles unconstrained once they reach the surface (Figure 1a). A top‐down imaging allows for a direct measurement of their location and size, as illustrated in Figures 1b–1e and detailed in a recent study focusing on the surface bubble dynamics (Néel & Deike, 2021). Drops, produced by the bursting surface bubbles, are imaged and detected from the side by means of telecentric shadow imaging, which preserves the true drop size across the depth of field.…”
Section: Contamination Controlled Optimal Productionmentioning
confidence: 99%
“…In between, an intermediate regime (Figures 1c and 1d) is characterized by similar sized, short‐lived bubbles that do not merge, assembling at most in small clusters before bursting, with between 0.1 and 1 bubbles per normalcnormalm2 ${\mathrm{c}\mathrm{m}}^{2}$. This intermediate regime is due to the decoupled evolutions of the bubble merging and bursting rates with respect to the surfactant concentration, the coalescence transition occurring at a lower concentration than the onset of the stabilizing effect (Néel & Deike, 2021). The measured bursting and merging rates for these conditions are given in the Supporting Information and Néel and Deike (2021).…”
Section: Contamination Controlled Optimal Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ocean surface is partly covered by a biofilm, which can be modeled with surfactants [25]. The surface-active contaminations are known to modify the static and dynamic behaviors of bubbles, including their coalescence, lifetimes, and bursting [26][27][28]. Consequently, the influence of the physicochemistry of the interface has to be taken into account in the process of bubble collapse at the interface and in the subsequent drop production.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the influence of the physicochemistry of the interface has to be taken into account in the process of bubble collapse at the interface and in the subsequent drop production. Néel & Deike (2021) [28] considered a monodisperse assembly of millimetric air bubbles produced identically in the bulk for a wide range of surface contamination and showed that, depending on the contamination, the bubble distribution that bursts can be very distinct from the initial distribution. There have been various experiments that attempted to described the role of the physicochemical parameters on the production of droplets by bursting bubbles [3,5,29,30], but there are large variations in protocols, and the influence of surfactants on the drop production remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%